Integral Backstepping Control for Maximum Power Point Tracking and Unity Power Factor of a Three Phase Grid Connected Photovoltaic System - Hicham Bahri; Mohamed Aboulfatah; M’hammed Guisser; Elhassane Abdelmounim; Mohammed El Malah (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents a robust control strategy for a grid connected photovoltaic system with a boost converter by using an integral Backstepping method based on a nonlinear state model, which guarantees the Lyapunov stability of the global system. The system has tracked precisely the maximum power point, with a very fast response and the unit power factor has been observed under different atmospheric conditions. Moreover, the best advantage of the controller is that it’s a good corrector of the grid perturbation and system parameter disturbance. The simulation result has demonstrated the performance of this strategy.